Growth and recovery in a time of default: Lessons from the role of the urban sector in Argentina - Michael Cohen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
International narratives on Argentina's recovery from the crisis of 2001-02 tend to emphasize the role of rising commodity prices and growing demand from China. Argentina is said to have been 'lucky', saved by global demand for its agricultural exports. The international narrative has also been used by local agricultural exporters to justify their objections against higher export taxes during periods of high commodity prices. These narratives are not correct. Data on the country's recovery show that it was not led by agricultural exports but was fuelled by urban demand and production. When the Convertibility period ended and the peso was devalued in 2002, price increases for imports stimulated the production of domestic goods and services for consumers. This production in turn generated multiplier effects which supported small and medium-sized firms and helped to create many new jobs. This later produced a revival of the construction and then the manufacturing sectors as well.
Keywords: O4; O54; R1; 330; economic crisis; urban sector; economic recovery